Effectiveness of Physical Exercise on Primary Dysmenorrhea Among Female University Students - Nyaga, Milcah Njoki; Muriithi, David (My University, 2017)
Primary Dysmenorrhoea is a condition that has attracted attention among the stakeholders in education and health professions. Primary Dysmenorrhea is chronic cyclical pelvic pain associated with menstruation in the absence of an identifiable pathological condition. Dysmenorrhea is one of the most common complaints and gynaecological problem worldwide among young females. Many females use pain killers such as paracetamol and Non-steroidal Anti Inflammatory Drugs (NSAIDS) to treat primary dysmenorrhea. The aim of this study is to investigate effectiveness of physical exercises on primary dysmenorrhea among University female students. The study adopted a descriptive research approach. It involved fifty students who had enrolled for gym at the University and had participated in regular exercise. The control group involved 50 students who had not enrolled for gym. The data was collected through self-administered questionnaires. The findings revealed that majority of the students were aware that exercise treats the symptoms of dysmenorrhea but they continued using painkillers. The study found out that majority of the students would consider exercise as an alternative therapy in treating the symptoms of dysmenorrhea. The study further revealed that the experimental group had late onset of menstruation and they took a longer time to menstruate as compared to controlled group. Overall the results of this study indicated that participating in exercise is a likely alternative approach to reduce the effects of primary dysmenorrhoea symptoms especially pain and improve the quality of life in young females.